2014
DOI: 10.3109/00207454.2013.872102
|View full text |Cite
|
Sign up to set email alerts
|

The significance of matrix metalloproteinase (MMP)-2 and MMP-9 in the ischemic stroke

Abstract: There is a continuous urgent need to explore the pathogenesis and biochemical changes within the infarcted area during acute ischemic stroke (IS). Matrix metalloproteinases (MMPs), prevailing extracellular endopeptideses, can digest proteins located extracellulary, e.g. collagen, proteoglycans, elastin or fibronectin. Among MMPs, gelatinases (MMP-2 and MMP-9) are the most investigated enzymes. Gelatinases possess the ability to active numerous pro-inflammatory agents as chemokine CXCL-8, interleukin 1β or tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 87 publications
1
85
0
3
Order By: Relevance
“…The characteristics of miRNA binding sites in mRNA of ZFHX3 gene and its orthologs S ome genes have been identified in stroke and they are considered as candidates to determine various subtypes of stroke (Mineharu et al, 2006;Kurzepa et al, 2014;Inose et al, 2015;Wu et al, 2017). These include the ZFHX3 gene encoding the transcription factor involved in the regulation of expression of many genes.…”
mentioning
confidence: 99%
“…The characteristics of miRNA binding sites in mRNA of ZFHX3 gene and its orthologs S ome genes have been identified in stroke and they are considered as candidates to determine various subtypes of stroke (Mineharu et al, 2006;Kurzepa et al, 2014;Inose et al, 2015;Wu et al, 2017). These include the ZFHX3 gene encoding the transcription factor involved in the regulation of expression of many genes.…”
mentioning
confidence: 99%
“…A reduction in MMP-2 and MMP-9 expression was observed following RB-222 treatment. It has been reported that the instant elevation of MMPs in acute ischemia-induced brain injury is involved in the digestion of the endothelial basal lamina and the triggering of secondary injury, including brain edema in acute stroke (8). The inhibition of MMPs promotes BBB restoration and neurovascular remodeling following stroke (9).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous proinflammatory agents that are trigged by ischemia can activate MMP expression immediately after a stroke (8). In acute ischemia, MMP-2 and MMP-9 in particular, mediated degradation of tight junction proteins (TJPs) in the BBB (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to the digestion of collagen type IV (a component of basal membranes), the transfer of leukocytes across the endothelium can be facilitated. 17 We determined that extracranial and intracranial ICA plaques, female gender had effect on MMP-2 levels. The present study also compared patients according to the presence of intracranial carotid DA, but there were no significant differences in terms of MMP levels or other parameters.…”
Section: Article In Pressmentioning
confidence: 99%